Faire avec l’industrie - Benjamin Raimbault (Revue d'anthropologie des connaissances)
This article questions the social and institutional conditions by which, in the context of the expansion of entrepreneurial science, proofs of concept become a vector of scientific credibility in engineering sciences. We argue that proofs of concept are a central vector of credibility that scientists in the engineering sciences establish to maintain and strengthen a hybrid position between academia and industry which is highly valued in their discipline. We emphasize the disciplinary efforts and the institutional conditions that enable the articulation between academic and economic rationales. Empirically, we focus on a scientific field at the crossroad between the life sciences and the chemical engineering sciences – metabolic engineering – and we trace the emergence of a specific proof of concept developed within this community: the metabolic pathway. We show that the credibility of the proof of concept is determined by the intermediate position of scientists between academia and industry, as well as by the support of technical universities.